Tatiana in Onegin’s life. Part I - Nikishov Yuri Mikhailovich (Studia Humanitatis)
The 200th anniversary of the first chapter of “Eugene Onegin” publication is approaching (February 2025). 200 years of the novel’s existence in its entirety is not so far away. There are countless interpretations of the main characters accumulated during this time. There are also separate assessments of them from the poet himself. Meanwhile, the author’s holistic view of the characters is still in shadows. Some important details remain unnoticed. Understanding the poet’s intention is a worthy goal for a researcher. Is it possible to consider that Tatiana became a part of Onegin’s life? It is possible if you notice that the hero and heroine exchanged mutual tender glances at their first meeting. It is possible, given that Onegin keeps an almost unnecessary letter from Tatiana. It is possible if Onegin manages to get rid of his egoism in his later life. This would also contribute to the renewal of his public position.